2021
DOI: 10.1177/20592043211022535
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Function with Value: An Exploration of Reasons to Engage and Disengage from Music Listening

Abstract: Investigations of music in everyday life are dominated by a functional perspective, drawn from work using the theory of Uses and Gratifications. In so doing, we may have neglected to fully appreciate the value people place on music listening. Therefore, the present study considered if, and why, people value music listening and probed instances when they may not want to listen to music in everyday life. A sample of 319 university students residing in Australia (76.50% female, M age = 20.64) completed an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 71 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Music can be used for numerous purposes, including arousal and mood regulation, social relatedness, and to achieve self-awareness (Schäfer et al, 2013). Relative to pre-COVID data, peri-COVID Australian data indicated that people emphasized value arising from music listening due to its ability to promote social connection, provide comfort and companionship, and counter loneliness (Krause, et al, 2023). Moreover, music choices can vary depending on social and environmental conditions (Pettijohn et al, 2012).…”
mentioning
confidence: 99%
“…Music can be used for numerous purposes, including arousal and mood regulation, social relatedness, and to achieve self-awareness (Schäfer et al, 2013). Relative to pre-COVID data, peri-COVID Australian data indicated that people emphasized value arising from music listening due to its ability to promote social connection, provide comfort and companionship, and counter loneliness (Krause, et al, 2023). Moreover, music choices can vary depending on social and environmental conditions (Pettijohn et al, 2012).…”
mentioning
confidence: 99%